การศึกษาแนวทางการยกระดับขีดความสามารถของผู้ประกอบการในห่วงโซ่อุตสาหกรรมชิ้นส่วนยานยนต์ไทยภายใต้ประชาคมเศรษฐกิจอาเซียน (THE STUDY OF LEVERAGING COMPETITIVENESS OF MANUFACTURERS IN AUTOMOTIVE PARTS INDUSTRIAL CHAIN UNDER ASEAN ECONOMIC COMMUNITY) - พรสิงห์, ชูศักดิ์; ธาราเวชรักษ์, ภัทรเวช; ทิวาพัฒน์, นพคุณ; ทองลิ่ม, ทองแท่ง (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2019)
การวิจัยในครั้งนี้มุ่งเน้นการศึกษาแนวทางการยกระดับขีดความสามารถทางเทคโนโลยีด้านวิศวกรรมของผู้ประกอบการผลิตชิ้นส่วนยานยนต์ไทยใน 3 กลุ่มองค์ประกอบ ได้แก่ กลุ่มตัวถังและตกแต่งภายนอก กลุ่มการตกแต่งภายใน และกลุ่มระบบห้ามล้อและการสะเทือน ซึ่งเริ่มจากการศึกษาข้อมูลทุติยภูมิเกี่ยวกับประสิทธิภาพ ศักยภาพ และขีดความสามารถทางเทคโนโลยีของอุตสาหกรรมผลิตชิ้นส่วนยานยนต์ไทยในสภาวะปัจจุบัน โดยนำข้อมูลมาสร้างเป็นแบบจำลองเพชร จากนั้นทำการสร้างแบบสอบถาม และแจกแบบสอบถามไปยังกลุ่มผู้ประกอบการที่ขึ้นทะเบียนกับสมาคมผู้ผลิตชิ้นส่วนยานยนต์ไทยกว่า 669 บริษัทได้รับแบบสอบถามกลับมา 197 บริษัท คิดเป็นร้อยละ 29.4 แต่หากคำนวณระดับความเชื่อมั่นของทาโร่ ยามาเน่ จะมีระดับความเชื่อมั่นที่ร้อยละ 94 ความต้องการเทคโนโลยีด้านวิศวกรรมในภาพรวมสามารถแบ่งออกเป็น 2 กลุ่ม คือ เทคโนโลยีกลุ่มแรกเป็นกลุ่มที่มีความต้องการอย่างเร่งด่วน ได้แก่ วิศวกรรมแม่พิมพ์ และวิศวกรรมดิจิทัล (CAD/CAM/CAE/Simulation/Automation) และกลุ่มที่สองเป็นกลุ่มที่มีความต้องการแต่ไม่เร่งด่วน ได้แก่ การขึ้นรูปชิ้นส่วนอลูมิเนียม การขึ้นรูปเหล็กกล้าความเค้นสูง และพลาสติกวิศวกรรม ด้านแนวทางการบูรณาการการยกระดับเทคโนโลยีสำหรับอุตสาหกรรมชิ้นส่วนยานยนต์ไทย ได้แก่ การสนับสนุนด้านการจัดตั้งศูนย์การทดสอบที่ได้มาตรฐาน การวิจัยและพัฒนาอย่างบูรณาการระหว่างภาคการศึกษาและภาคอุตสาหกรรม การร่วมมือระหว่างรัฐบาลกับภาคเอกชน คำสำคัญ: เทคโนโลยีด้านวิศวกรรม อุตสาหกรรมผลิตชิ้นส่วนยานยนต์ This research is about to study the courses of leveraging competitiveness of engineering technologies of Thai automotive parts manufacturers in 3 compositions; body and exterior parts, interior parts, and brakes and suspension systems. The study started with the reviewing of the secondary data about the current situation of performance, potential, and competitiveness of Thailand automotive part industry chain. The diamond model was deployed to analyze and depicted the information. Then, the questionnaire from was created and distributed to 669 companies who registered with the Thai auto parts manufacturers association. There were 197 companies answered the questionnaire. As a result, the questionnaire response rate was about 24.9%. However, the confidence level was 94% with Taro Yamane’ sampling theory. The data analysis results showed that the engineering technologies requirement was divided into 2 groups: the first one was an urgent requirement which were mold engineering and digital engineering (CAD/CAM/CAE/Simulation/Automation), the second one was non-urgent requirement which were aluminum forming, high-stress ​​steel forming and plastics engineering. The integration of leveraging competitiveness for Thai automotive parts industry were to support the standard testing center settlement, integration between academic and industry on research and development, and cooperate between the government and private sectors. Keywords: Engineering Technology, Thailand Automotive Part Manufacturers